Brilliant Corruptions: Scribal Influence on Variation in the Coffin Texts - Grotenhuis, Jorke (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
In this paper, it is intended to put a spotlight on some of the more interesting sections of the Coffin Texts, originating from human error, visible in the variation between the witnesses. Besides showing the sections of text with these variations, explanations are provided on how the distinct variations could have occurred. For this paper, three topics of variation will be discussed: Variation due to errors caught by the scribes, variation due to redaction, by replacing pronouns with the name of the owner or changing double columns into singular columns or by abbreviating sections of text and finally variations due to homophony.